(untitled) (Journal of Hama University, 2024)
Introduction: Cervical cancer is the fourth most common cancer among women in the world despite being a highly preventable and treatable cancer. The Aim: To assess women’s knowledge, beliefs and practices about the Pap smear test for cervical cancer. Material &methods: A descriptive, quantitative, cross-sectional study was conducted on an appropriate sample of (100) women attending primary health care centers in Lattakia Governorate. Data were collected during the period from April 1, 2022 to May 5, 2022. A structured questionnaire was completed on sociodemographic information, and data were assessed and collected through a 35-item scale on women’s information, beliefs, and practices about the smear. The results : The results showed that most women (83%) had heard of the smear, but about half (48%) do not know that it should be done every 3 years, and more than half (59%) believe that it is able to detect cancer before it occurs, and more than half (53%) had not heard of the human papillomavirus vaccine. With regard to practice, it was found that (35%) had taken the smear, noting that (66%) find encouragement from the husband, and more than two-thirds (77%) have no difficulty in reaching the center. health, but the majority (83%) would be concerned if early signs of illness were detected. Conclusion & Recommendations: We conclude from the study that women have a varying level of information with a positive belief, but the practice is weak with regard to conducting the smear, and therefore there is a need for more awareness and education about the importance of conducting the smear with the need for a national strategy for it within health centers